Influence of crop regulation on growth, yield and quality of purple passion fruit (Passiflora edulis) - LALMUANPUII, R; HAZARIKA, T K; NGURTHANKHUMI, RODY; PANDEY, S K (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2021–22 and 2022–23 at Mizoram University, Aizawl, Mizoram to assess the impact of flower and fruit thinning and growth regulating chemicals on yield attributing characters, yield, and quality of purple passion fruit (Passiflora edulis Sims.). The experiment was laid out in randomized block design (RBD) with 14 treatments, viz. T1, Control; T2, Flower thinning; T3, Manual fruit thinning; T4, GA3; T5, ethephon; T6, Forchlorfenuron (CPPU); T7, Flower thinning + GA3; T8, Flower thinning + ethephon; T9, Flower thinning + CPPU; T10, Flower thinning + GA3 + ethephon + CPPU; T11, Manual fruit thinning + GA3; T12, Manual fruit thinning + ethephon; T13, Manual fruit thinning + CPPU; T14, Manual fruit thinning + GA3 + ethephon + CPPU. The results indicated that crop regulation with manual fruit thinning + GA3 + ethephon + CPPU (T14) was the most effective in terms of highest fruit set percentage (58.92%), minimum fruit drop (38.22%), maximum yield/vine (10.52 kg), fruit weight (56.60 g), TSS (15.85°Brix), total reducing and non-reducing sugars (11.53, 8.80, 2.59%), ascorbic acid (35.56 and 36.93 mg/100 g), carotenoid (3.32 mg/100 g), and total phenols (23.16 mg GAE/100 g). This study recommends that treatment involving manual fruit thinning + GA3 + ethephon + CPPU is considered as best crop regulating technique in commercial passion fruit cultivation to improve yield and fruit quality.